Party cues and yardstick voting; Parteien und 'Yardstick'-Wählen - Benny Geys; Jan Vermeir (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
Politicians within any given party generally exhibit a degree similarity in terms of (political) viewpoints. Moreover, they are often constrained to follow general party lines on certain policy issues. Finally, they may be more likely to mimic one another than politicians from another party. Hence, parties provide important cues on how politicians will act once elected. The present paper assesses the implications of such party cues for the traditional model of yardstick voting (where voters use what they observe in neighbouring jurisdictions to judge the performance of their incumbent). It is shown that the information content of what happens in neighbouring jurisdictions differs depending on whether or not the same party governs this jurisdiction. More specifically, we find that voters might still take neighbouring jurisdictions into account, but should distinguish between jurisdictions where the same or a different party is in power. The results of the model are in line with recent empirical observations in Sweden and the United States. – – Politiker einer beliebigen Partei zeigen gewöhnlich Ähnlichkeiten bezüglich (politischer) Ansichten. Zudem sind sie in bestimmten Politikfeldern oft abhängig von Grundsätzen ihrer Partei. Letztlich übernehmen sie Standpunkte eher untereinander als von Politikern anderer Parteien. Daher liefern Parteien wichtige Hinweise wie Politiker nach ihrer Wahl handeln werden. Das vorliegende Papier beurteilt die Auswirkungen solcher Informationen über die Partei auf das bekannte ,,Yardstick Voting“ Modell (Wähler nutzen ihre Beobachtungen aus benachbarten Regionen zur Beurteilung ihrer eigenen Regierung). Es wird gezeigt, dass der Informationsgehalt der Ereignisse in Nachbarregionen stark davon abhängt, ob dieselbe Partei die Regierung stellt. Genauer gesagt, Wähler können andere Regionen bei ihren Entscheidungen berücksichtigen, jedoch sollten sie zwischen solchen mit derselben und mit einer anderen Partei in der Regierungsverantwortung differenzieren. Die Ergebnisse des Modells decken sich mit jüngsten Beobachtungen in Schweden und den Vereinigten Staaten.
Keywords: D72; H30; H77; 330; Yardstick voting; spatial interaction; party labels; party cues